Normalization of Gender Bias Regulations in Pondok Pesantren: Normalisasi Regulasi Bias Gender di Pondok Pesantren - Isnaini Nuruddin Akbar (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
Pesantren that has respective objective to produce pious person, in some aspect perpetuates differenrdiscriminativees for female studetns. This study shows mainstream gender constructionin Islamic boarding school regulations forms of gender discrimination and their implications. The object of study includes three pesantren in the Singosari, East Java, Indonesia. The regulations of the pesantren follows scholars’ ideology as written in the classical book (kitab kuning), which portrays men as family leader and the ideal position of women as male companions. The teaching of kitab kuning in the pesantren regulations has led female students to experience discrimination in carrying out their daily lives in the pesantren environment . Female students are not allowed to go outside the building at night, they are only allowed to go out during the day and even then it is limited to certain schools and streets. From the results of interviews, this study found that these rules had a great influence on their lives. Keywords: Normalization, gender, regulation, pesantren